The Southeastern Librarian, Vol.35, No.3, Fall 1985 - Lucas, Linda (The Southeastern Library Association, 1985)
The Southeastern Librarian, Vol.35, No.03, Fall 1985. Periodical.
1 electronic record. 32 pages. Scanned from original document. Contents Include: Linda Lucas- Editor's Page- 67, Rebecca Bingham- From the President's Desk- 69, Carolyn Baggett- Serving the "Beasts" in the "Fair Garden"- 70, Celia Hales- Basic BI at the University of North Carolina at Charlotte: Results of an Experiment- 76, Barbara B. Moran- Survey Research for Librarians- 78, Dates to Remember- 86, SELA Chronicle- 87, Regional News- 87
Keywords: Periodicals | Southeastern Library Association